(untitled) (Research, Society and Development, 2025)
Dentistry in Brazil is a professional activity regulated by norms that establish rights and responsibilities. However, the increase in lawsuits reflects the complexity of issues related to dental practice and civil liabilities. With the regulation of the specialty of Orofacial Harmonization, an even greater growth in such claims is expected due to the involvement of aesthetic procedures. The objective of this study was to evaluate the evolution of these legal disputes in the period from 2019 to 2024. To achieve this, a cross-sectional study was conducted using a public domain website (www.jusbrasil.com.br), employing the term “dentist” and procedures related to the specialty in the jurisprudence section, covering courts of justice across the entire national territory. A total of 45 court decisions were identified, with the majority concentrated in the state of São Paulo. Between 2019 and 2024, a gradual increase in the number of cases was observed, except for the year 2023, with non-surgical procedures being the most frequently contested. The compensations set in the lawsuits showed that claims for moral damages had a more significant financial impact compared to material damages, with a mode of R 15,000.00. Thus, it is emphasized that professionals must adopt ethical conduct and base their practices on high standards, ensuring patient safety and compliance with current regulations.